Biopolymers of Chitosan-Anthocyanin From Purple Sweet Potatoes (Ipomoea Batatas L.) Extract and Their Interaction with Formalin - F. Widhi Mahatmanti; Harjono; Mohammad Alauhdin; Riska Putri Mawarni (Indonesian Journal of Chemical Science, 2024)
Purple sweet potato is one of the potential sources of anthocyanins. Anthocyanins can be utilized in various fields, such as sensors. Chitosan biopolymer allows formulation with anthocyanins because it possesses biodegradable and antimicrobial properties, and it does not inhibit color changes from anthocyanins. This study aims to prepare anthocyanins from purple sweet potatoes, formulate chitosan-anthocyanin biopolymer (CAB), and test the effect of time and formalin concentration on color changes in CAB. The research results show: 1) anthocyanin extract (TAC) from purple sweet potatoes is 852 mg/L with anthocyanin monomer (cyanidin) of 443.03 mg/500 g or 88.61 mg/100g. Anthocyanin extract at pH 1-12 has colors ranging from red to brownish-yellow; 2) CAB was successfully formulated with anthocyanin extract from purple sweet potatoes, chitosan, and glycerin. BKA-A was obtained with a content of 10 mL anthocyanin extract and CAB-B with 15 mL anthocyanin extract; 3) the produced biopolymers have average swelling values of 444% (CAB-A) and 339.5% (CAB-B). The storage time of CAB-B is longer than CAB-A. FTIR analysis showed a broad peak at ~3336 cm-1 indicating hydroxyl groups from anthocyanin extract; and 4) ANOVA test results showed that interaction time and formalin concentration affect color changes in CAB-A partially, while color changes in CAB-B are only influenced by interaction time with formalin.